A Methodological Approach to Assess the Climatic Potential of Natural Ventilation Through Façades - Nejmia Ali Mohammed; Gabriele Lobaccaro; Francesco Goia; Gaurav Chaudhary; Francesco Causone (Journal of Facade Design and Engineering, 2019)
Due to the rapid development of super insulated and airtight buildings, the energy requirement for mechanical ventilation is becoming more and more dominant in today’s highly efficient buildings. In this scenario, natural ventilation has the potential to reduce energy use for buildings while maintaining ventilation rates that are consistent with acceptable indoor air quality. The increase in air temperature and frequency of extreme weather events (e.g. heavy rains, heat and cold waves) due to climate change will alter future outdoor boundary conditions and consequently the potential for natural ventilation in buildings. Therefore, to respond to the fluctuations in outdoor boundary conditions, the building envelope should become more and more dynamically responsive. In that sense, the façade plays an important role by regulating indoor comfort based on outdoor environmental conditions. This paper presents a methodological approach to investigate the potential of natural ventilation through the façade in office buildings in present and future climate conditions. It reviews technologies and strategies that maximise the use of natural ventilation in office buildings located in six selected different European climates. Numerical analyses were conducted, considering outdoor air temperature and humidity. Integrated façades with hybrid systems and strategies is one of the key solutions for increasing the potential of natural ventilation. The results showed that a hybrid solution with low-pressure drop heat recovery had the greatest potential to maximise the possibilities of low energy façade integrated ventilation.